ANALISIS KESULITAN PESERTA DIDIK DALAM MENENTUKAN IDE POKOK PADA TEKS CERITA NARASI KELAS lV SD NEGERI BABADSARI - Bayu Fatah Alam; Titi Anjarini; Muflikhul Khaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to 1) The difficulties experienced by students are not yet mastering the main idea, difficulty in determining the main sentence and difficulty when finding sentences that are too long in a paragraph. 2) Students have difficulty in determining the main idea and explanatory ideas/supporting ideas. to find out the difficulties of students in determining the Main Idea in Narrative Story Texts of Grade IV Elementary School Babadsari. This type of research is descriptive qualitative. The subjects of the study were 18 grade IV students of Elementary School Babadsari. The object of the study was the results of student tests on the main idea of ​​the paragraph in the reading text "Environment" this study was conducted to determine the difficulties of students in determining the main idea of ​​the paragraph and to determine the factors of students' difficulties in determining the main idea of ​​the paragraph. Data collection techniques used interviews, observations, and documentation. Data collection instruments used interview guidelines, and observations. This study used source triangulation. Data analysis includes 1) Data collection; (2) data reduction; (3) data presentation; 4) drawing conclusions. The results of the study are that students have the ability to determine the main idea of ​​a paragraph in a narrative text, namely that students assume that the main idea of ​​a paragraph in a narrative text is always in the first paragraph. Factors that cause students' difficulties in determining the main idea of ​​a paragraph include the lack of reading the narrative text to the end and also many students who do not pay attention during the learning process. Based on the results of the test conducted with 3 questions 1 narrative text, 11 students were able to answer correctly, while 7 other students were still unable to answer correctly.